Growth and Characterization of M-Plane GaN on \(γ\)-LiAlO2 (100) Substrates by Plasma-Assisted Molecular Beam Epitaxy - Lin , Yu-Chiao; Lo, Ikai; Shih, Hui-Chun; Chou , Mitch M. C.; Schaadt , D. M. (New Frontiers in Physical Science Research Vol. 5, 2022)
On LiAlO2 substrates, M-plane GaN thin films were produced using plasma-assisted molecular beam epitaxy at various N/Ga flux ratios. As the N/Ga flux ratio decreased, the GaN surface trended to a flat morphology with stripes along [11\(\bar{2}\)0] and exhibited a better crystal quality. This trend had been investigated that the substrate could be damaged by N2 plasma during the high N/Ga flux ratio growth condition and easily cause the formation of Li5GaO4 on the interface between GaN and substrate.